Surface epithelium related activation of complement differs in Crohn's disease and ulcerative colitis. Issue 7 (July 1992) - Halstensen, T S; Mollnes, T E; Garred, P; Fausa, O; Brandtzaeg, P
Abstract : IgG1 and activated complement are colocalised on the colonic epithelial brush border in active ulcerative colitis. To investigate whether such deposition is specific for ulcerative colitis, we examined ethanol fixed mucosal specimens from 18 patients with Crohn's colitis and 14 with terminal ileitis by indirect two colour immunofluorescence staining. Monoclonal antibodies to the IgG subclasses and to neoepitopes of activated complement C3b and the terminal complement complex were used in combination with rabbit antiserum to C1q, C4c or cytokeratin. Granular deposition of C3b and terminal complement complex were observed at the luminal face of the surface epithelium in 10 of 18 patients with Crohn's colitis. Specimens from eight of 14 patients with ileal involvement were intensely stained for activated complement (primarily C3b) within the surface mucus layer. No epithelial IgG, C1q or C4c deposition was observed. The results suggest that early and late phase complement activation takes place at the luminal face of the epithelium in Crohn's disease. The absence of colocalised IgG and complement components involved in the classical activation pathway (C1q and C4c), however, suggest that other immunopathological mechanisms (the alternative pathway?) are primarily involved in Crohn's disease in contrast with ulcerative colitis.